Trichothecene genotypes and production profiles of Fusarium graminearum isolates obtained from barley cultivated in Argentina - Castañares, Eliana (2014)
Fusarium graminearumis one of the most important pathogens isolated from small cereal grains with Fusarium Head Blight symptoms. The presence of this fungus is often linked to the occurrence of several mycotoxins in barley and wheat. The aim of our study was to characterize trichothecene genotypes and production profiles ofF.graminearum sensu strictoisolates obtained from barley grains in Argentina. A total of 110F.graminearum s.s. isolates were analyzed by PCR assays to predict deoxynivalenol (DON), 15-acetyldeoxynivalenol (15-ADON), 3-acetyldeoxynivalenol (3-ADON) and nivalenol (NIV) production, and all isolates were found to belong to the same molecular 15-ADON genotype. Trichothecene production in autoclaved rice was analyzed by using gas chromatography (GC) and confirmed by GC–MS. Of the 110 isolates, 95% were able to produce DON, 71% produced 15-ADON, 63% 3-ADON and 52% NIV. With the exception of a single isolate, all isolates that produced NIV, also produced DON. However, the NIV production was very low, ranging from 0.13 to 0.30μg/g. Six different production profiles of DON and its acetyl-derivatives were detected, the predominant being simultaneous production of DON, 3-ADON and 15-ADON, followed by DON production, and DON and 15-ADON co-production. This work is the first attempt to characterize the trichothecene genotypes and production profiles ofF.graminearum s.s. isolates from Argentinean barley.